2004
DOI: 10.1080/10242420400010523
|View full text |Cite
|
Sign up to set email alerts
|

α-Chymotrypsin shows higher activity in water as well as organic solvents after three phase partitioning

Abstract: Alpha-Chymotrypsin was found to show a 119% increase in activity after three phase partitioning. The k cat /K m of the partitioned enzyme (TPP-C ) for hydrolysis of BzTyr-OEt in aqueous medium at 258C was found to be 48.3/10 4 mM 1 min 1 as compared to the corresponding value of 17.7 /10 4 mM 1 min 1 for the untreated control (C ). The l max of the fluorescence emission spectrum of TPP-C showed 178% increase in the quantum yield when compared to C. TPP-C showed a 2.94 and 3.58 fold increase (as compared to C )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…TPP treatment has, in many cases, resulted in improvement of the catalytic rates of the various enzymes by the marginal to moderate degrees [23,24,[28][29][30][31]. As indicated in the introduction, TLL subjected to TPP under optimized conditions showed an increase in the initial rates of hydrolytic activity from 8.6 to 17.8 U/mg protein ( Table 1).…”
Section: Activity Of Tll and Tpp-tllmentioning
confidence: 88%
See 4 more Smart Citations
“…TPP treatment has, in many cases, resulted in improvement of the catalytic rates of the various enzymes by the marginal to moderate degrees [23,24,[28][29][30][31]. As indicated in the introduction, TLL subjected to TPP under optimized conditions showed an increase in the initial rates of hydrolytic activity from 8.6 to 17.8 U/mg protein ( Table 1).…”
Section: Activity Of Tll and Tpp-tllmentioning
confidence: 88%
“…The complexity of the mechanism by which it works was discussed adequately by Lovrein et al [27], and more recently in the context of protein refolding [26]. There have been quite a few reports on the effect of TPP treatment on the structure and function of many enzymes and proteins [21][22][23][24][25][26][27][28][29][30][31]. In few cases, it has been clearly shown that the specific activity of the pure enzyme increased after being subjected to TPP [24,25,29].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations